Study on Lime and Fly Ash as a Stablizing Agent on Soil Subgrade (International Journal of Innovative Research in Engineering & Management, 2023)
Today, poor soil properties constitute a significant issue in engineering projects. Sometimes altering the qualities of the wrong soil is the first step in construction. Pavement that collapses too quickly is one of the early warning indications of degradation in pavement systems on poor soil subgrades. In most cases, clayey soil has the potential to have unfavourable engineering characteristics like low bearing capacity, high shrinkage and swell characteristics, and high moisture susceptibility. Stabilizing these soils is a typical method to improve their tensile strength. A process known as soil stabilisation adds a binder to the soil in order to improve the engineering performance of the soil.
Keywords: Lime; Fly ash; Clayey soil; Admixtures; CBR; Soil stabilization; Index; Engineering properties